Smart Bin Design Based on Global System for Mobile Communications Modem and Ultrasonic Sensor Interface using Arduino Uno Board as Platform - Narcisa Morallo (JPAIR, 2017)
The more urbanized and industrialized a country becomes, the more trash it produces. Waste management has been a crucial issue to be considered.  In this paper, a smart bin using GSM (Global System for Mobile communications) modem and ultrasonic sensor interface with Arduino Uno board as platform is proposed and prototyped. Technology in arduino, ultrasonic sensor and GSM module are reviewed. The GSM module is an open, digital cellular technology used for transmitting mobile voice, data services and transmission of SMS (Short Message Service). Ultrasonic Ranging Module, HC - SR04, is placed on the cover of the dustbin which will determine the status of the garbage inside. The minimum level of garbage inside the dustbin is 10 cm. Once the garbage reaches the minimum level, HC - SR04 ultrasonic sensor triggers the GSM modem which will continuously alert the required authority until the garbage is removed from the dustbin. Design shows that GSM modem and ultrasonic sensor interfacing using Arduino Uno board as platform can make garbage collection operations smarter, more efficient and less wasteful. To be more energy-efficient, solar power will be incorporated into future designs.